The Effect of Using Face Primer Gel on Oily Facial Skin Bridal Makeup Results - Pratiwi, Ervina Vivin; Dewi, Siska Miga; Azhari, Nadya (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2023)
This research started from the results of pre-study observations on West Sumatran brides who have oily facial skin, it was found that there were problems with inappropriate makeup results that affected their appearance and self-confidence, including makeup that didn't last long. and form the powder gathered in one place. This study plans to investigate the impact of the use of face primer gel on the makeup results of West Sumatran brides with oily facial skin. This type of examination is an investigation with a quantitative methodology. The number of samples in this exploration were Padang State University students with an age range of 19 – 25 years with the criteria of having oily facial skin. The sample collection technique used a purposive testing technique with a sample size of 2 individuals. Search information using One Sample T-test with SPSS 25. Due to the use of face primer gel in West Sumatran bridal cosmetics on oily facial skin, it can be seen that the most prominent value is in the smoothness level with a normal value of 3.70 with a very smooth model. In the flatness section, it has a normal 3.80 with a very normal model. Meanwhile, in terms of durability, it has a typical value of 3.80 with a very durable size.